Eksplorasi Kendala Guru Pemula Dalam Mengimplementasikan Kurikulum Merdeka Belajar - Rosita Ovi Adelia; Catur Febhian Sukma Indrawati; Agung Setyawan (Suria Academic Press, 2026)
This study aims to explore the various challenges faced by novice teachers in implementing the Merdeka Curriculum at the elementary school level. Using a qualitative descriptive approach with a case study design, data were collected through literature studies. The findings indicate that novice teachers encounter multidimensional challenges, including conceptual-pedagogical limitations, technical difficulties in designing differentiated instruction, structural barriers such as limited resources, and psychological pressures such as stress and fatigue. Despite their strong enthusiasm, teachers often struggle to translate curriculum concepts into classroom practice and to effectively manage heterogeneous classes. The study concludes that systemic support through structured mentoring programs, collaborative learning communities, and the provision of adequate facilities is essential to enhance the professionalism of novice teachers and ensure the successful implementation of the curriculum.